Przemówienie na Wawelu – Józef Piłsudski o tradycji i spuściźnie wielkiej poezji romantycznej - Sztankóné Stryjniak, Elżbieta (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2013)
In the article, the rhetoric investigative apparatus is used to analyse the speech delivered by Józef Piłsudski on 28 June 1927 on the occasion of placing Juliusz Słowacki’s remains in the Royal Tombs at Wawel Castle. The analysis allowed for distinguishing the most important ideas communicated in the speech. These include: - - liberty as the greatest value in the life of both the individual and the whole nation; - - man as the subject of history; - - the utmost importance of the romantic tradition in the history of Poland. Furthermore, the analysis has revealed distinctive features of the occasional speech that is typical for spectacular oratory (genus demonstrativum).